2021
DOI: 10.1002/ajmg.a.62592
|View full text |Cite
|
Sign up to set email alerts
|

Giant axonal neuropathy (GAN) in an 8‐year‐old girl caused by a homozygous pathogenic splicing variant in GAN gene

Abstract: Giant axonal neuropathy (GAN) is a progressive disease that involves the peripheral and central nervous systems. This neurodegenerative disease is caused by variants in the GAN gene encoding gigaxonin, and is inherited in an autosomal recessive manner. Herein, we performed whole‐exome sequencing on a 8‐year‐old child with dense, curly hair, weakness in both lower limbs, and abnormal MRI. The child was born to consanguineous parents. Our results revealed that the child carried the c.1373+1G>A homozygous pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
2
1
0
Order By: Relevance
“…This is confirmed by studies that reviewed over 63 reported cases of the GAN variant [9]. These findings were echoed by Guo et al [10] who also investigated 55 cases of the GAN variant showing clinical features that are compatible with the clinical presentation of our cases. Moreover, determining the severity and prognosis of patients remains an active area of research.…”
Section: Discussionsupporting
confidence: 89%
“…This is confirmed by studies that reviewed over 63 reported cases of the GAN variant [9]. These findings were echoed by Guo et al [10] who also investigated 55 cases of the GAN variant showing clinical features that are compatible with the clinical presentation of our cases. Moreover, determining the severity and prognosis of patients remains an active area of research.…”
Section: Discussionsupporting
confidence: 89%
“…Data analysis of 55 cases of GAN was published by Guo et al ( 2022 ) show that hypo/areflexia, muscle weakness, curly hair, and cerebellar dysfunction were the most detected clinical findings that are compatible with the clinical presentation of our cases. The most commonly reported electrodiagnostic and neuroimaging findings in GAN include sensorimotor neuropathy and nonspecific supra and infratentorial white matter signal changes, respectively.…”
Section: Discussionsupporting
confidence: 86%
“…Progressive distal motor weakness is the initial symptom in all cases. Diffused muscle atrophy, most predominantly in distal muscles, flaccid, paralysis, severely decreased muscle strength, low muscle tone, and loss of reflexes (areflexia) may be observed as the disease advances ( Table 2 ) [ 3 , 22 , 23 , 24 , 25 , 26 , 37 , 38 ]. Diagnosis of PNS degeneration in early infancy and sensorimotor pathway involvement in teens resemble more commonly inherited peripheral neuropathy called Charcot-Marie-Tooth (CMT) diseases [ 27 ].…”
Section: Clinical Heterogeneity In Persons With Ganmentioning
confidence: 99%